PEMBERIAN IZIN TERHADAP PENJUALAN MINUMAN BERALKOHOL DITINJAU BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 6 TAHUN 2003 TENTANG LARANGAN, PENGAWASAN, PENERTIBAN PENJUALAN MINUMAN BERALKOHOL - Muhamad Syamsudin (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACT Permit as proof of legality to run a business, especially trading goods that are sold freely or goods whose trade is under government supervision. One of the merchandise which is controlled by the government is alcoholic drinks. Alcoholic drinks are included in the merchandise under surveillance because the effects of consuming alcoholic drinks can reduce or eliminate people's awareness and cause illness in the human body.This type of research used in this research is Normative law research.